A Computational Bibliometric Analysis of E-Groceries Analysis Using VOSviewer - Lesmana, Rudhi; Rifaldi, M Ihsan (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
The purpose of the research is to combine mapping analysis with VOSviewer as well as Publish or Perish software to do a computerized bibliometric analysis of the topic "E-Groceries Analysis." The method used descriptive-quantitative approach in conjunction with bibliometric analysis in which the data were retrieved from Google Scholar. Based on the results, E-Groceries Analysis research decreases every year, proven by the fact that 2018 have 25 articles and increased to 32 articles in 2019, 49 articles in 2020, and 98 articles in 2021. Based on further findings of this research, it can be concluded that there are several understudied sectors in E-Groceries Analysis that may be examined further to increase the efficacy of E-Groceries analysis. This research is also anticipated to serve as a reference for future research in defining and assessing the research subject, as well as a reference for field to be studied in E-Groceries analysis.